If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 185x + (-7624) = -12790 185x + -7624 = -12790 Reorder the terms: -7624 + 185x = -12790 Solving -7624 + 185x = -12790 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7624' to each side of the equation. -7624 + 7624 + 185x = -12790 + 7624 Combine like terms: -7624 + 7624 = 0 0 + 185x = -12790 + 7624 185x = -12790 + 7624 Combine like terms: -12790 + 7624 = -5166 185x = -5166 Divide each side by '185'. x = -27.92432432 Simplifying x = -27.92432432
| 6s-12=7 | | 7n-3=102 | | 72/2016 | | (x-4)/-4=-10 | | 5-8=6x-5x+9 | | 0.5(t-12)=1.5-3 | | 9y^2+144=0 | | 4x=(6x/12) | | 12xsquared+3=4 | | 0.32+10=26 | | -12+3x=9 | | (x^2-9)(x^2-16)-15x^2=0 | | (-2/3)(x-3)-x=8 | | 5/2x-7=-2 | | (x^2-9)(x^2-16)-15x=0 | | 24.1=9.61+x^2 | | -3(x-4)+x=10 | | -8n+4(1+5m)=-6n-14 | | .50(x+2)=-6 | | 33=-22a+7 | | 35=7+4 | | 3/12=3/4 | | 8/5p=24 | | Y=120x-60x^2 | | -3.72-4.58= | | (x^2-9)(x^2-16)=15x | | 3=5s+15 | | 5x+7-7x=13-15x+13x-6 | | 4x-(x/2)-3=(1/2) | | 9r+12=24 | | 6(x-9)+x=7(x+8)+2 | | 41666666667= |